Delineation of karst terrain using resistivity method - Bakhshipour, Zeinab (2011)
This thesis describes the application of the Electrical Resistivity (ER) method in delineation subsurface of structures and cavity carried out in Kuala Lumpur Limestone within Batu Cave area, Selangor Darul Ehsan, Malaysia. The Kuala Lumpur limestone is well known for its highly erratic karst features. ER methods have proven to be efficacious in many studies involving environmental and engineering problems, and have been used in order to locate and delineate subsurface features and estimate the physical properties associated with the soil. In fact the major advantage of the ER method is that the soundings can be performed in a relatively short time and in a confined space. ER surveys can map high conductivity anomalies over filled sinkholes and soil pipes that penetrate the unconsolidated cover. Inverted ER sections made over these anomalies can depict filled sinkholes, fractures and cavities as conductive zone over deeply weathered bedrock. Wenner electrode configuration was employed for the field survey which was carried out for seventeen profiles to provide continuous coverage. The ER profiles (1520m in total length) were measured using a Wenner electrode configuration with 2m spacing. Color-modulated sections of resistivity versus depth were plotted for all lines, giving an approximate image of the subsurface structure. The field survey was accompanied by laboratory work. The resistivity of rock, soil and water samples taken from the field was determined in the laboratory and resistivity formation factors were obtained. The relationship between resistivity and formation factors for all samples was established. The porosity of the each sample was also calculated and a relationship between the porosity and formation factor was established. The established relationship was applied to the data obtained in the field in order to calculate the porosity values of the formation present within the exploration area. The porosity values were plotted and contoured. Depth to the bedrock for each line was obtained from the electrical resistivity in the field work. A 2-dimensional (2D) and 3-dimensional (3D) representation of the subsurface topography of the area was prepared using commercial computer software. The use of the software also enabled visualization of the subsurface features of the limestone investigated in the present work.